ANALISIS KINERJA GURU BERSERTIFIKAT DI SMA NEGERI 7 BULUKUMBA - Fadhilah, Fadhilah (Eklektika: Jurnal Pemikiran dan Penelitian Administrasi Pendidikan, 2017)
This study is intended to describe the performance of certified teachers and factors that influence the SMA Negeri 7 Bulukumba. This type of research is qualitative research with data sources are principals, heads of administration, curriculum officers, certified teachers, and students. The techniques used in data collection are interviews, observation, and documentation. The data obtained were analyzed by qualitative descriptive analysis.The results showed that the performance of certified teachers in SMA Negeri 7 Bulukumba was seen from the results of work, work efficiency, job satisfaction and work adaptation went well and the most prominent in improving the performance of certified teachers. This can be seen from certified teachers who have a performance in the success of learning, increasing the absorption of students is proven by the methods and media of learning. Factors affecting the performance of certified teachers in SMA Negeri 7 Bulukumba seen from internal and external factors, these two factors strongly support the implementation of the learning process well, it can be seen that the better the teacher's personality, the higher his dedication in carrying out his duties but the means and infrastructure is not sufficiently supportive, which prevents teachers from carrying out their duties.